Interactions Between Tropical Cyclones and the Midlatitude Waveguide: Downstream Impacts and the Role of Convective Processes - (:unkn) unknown (My University, 2022)
Significant amplification to the waveguide can occur when a recurving tropical cyclone (TC) interacts with the midlatitude flow, leading to significant downstream impacts. To this point in time, TC-midlatitude waveguide interactions have been conceptualized as primarily being driven by large-scale processes, with convective-scale contributions having been parameterized or neglected. This three-part study diagnoses the impact TC-midlatitude waveguide interactions have on the intensity evolution of downstream TCs and the role convective-scale processes play in TC-midlatitude waveguide interactions. Recurving TCs in both the North Atlantic and western North Pacific basins frequently interact favorably with upstream troughs, where a favorable interaction entails the tightening of a pre-existing potential vorticity (PV) gradient on the eastern flank of the trough, leading to subsequent downstream flow amplification in the vicinity of a downstream TC. In the Atlantic, weakening downstream TCs are closer to the midlatitude waveguide on the southeastern edge of the amplified midlatitude ridge, whereas strengthening downstream TCs are further from the waveguide and equatorward of the amplified midlatitude ridge. Conversely, western North Pacific strengthening and weakening secondary TCs are primarily stratified by latitude, with weakening secondary TCs located poleward of their strengthening secondary TC counterparts. Convective-scale processes are shown to potentially play a role in determining the strength and downstream evolution of TC-midlatitude waveguide interactions. This importance of convective-scale processes on the large-scales is accomplished by way of an inverse energy cascade supported by the filamentation of intensely negative PV generated by deep, moist convection. These negative PV anomalies are generated by intense horizonal gradients of diabatic warming and exist primarily in the middle- to upper-troposphere. While preliminary sensitivity simulations suggest that convective-scale processes in particular regions of a TC-midlatitude waveguide interaction may not play a key role in determining the strength, and subsequent evolution of the interaction, that is not to say that convective-scale processes do not play a role at all. Additionally, the relative importance of convective-scale processes may depend on the particular TC-midlatitude waveguide interaction being studied.
Keywords: Convection; Cyclone; Tropical; Waveguide